(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
During years, when a new inscription was found and it had new names that were not documented in any onomastic list they were catalogued as hapax. Basing on the Cabuniaegino’s ara, from Monte Cildá (Olleros de Pisuerga, Palencia), in which all its names were considered hapax legomenon, we propose some caution before regarding it.